Man of the year [videorecording (DVD)] - Levinson, Barry; Levinson, Barry; Levinson, Barry; Williams, Robin, 1951-2014; Walken, Christopher, 1943-; Linney, Laura; Goldblum, Jeff, 1952-; Black, Lewis, 1948- (Universal Pictures, 2007)
Tom Dobbs makes an off-hand comment on his late night talk show that he would be a better president than the leader who currently occupies the White House. A grassroots campaign conducted by his legions of fans finds him unexpectedly ushered into the Oval Office and forced to live up to his promise. Unfortunately for Dobbs, he finds out that his surprise victory was actually the result of a voting computer glitch and not winning the majority vote leaves the outspoken funnyman struggling with the decision to stay the course in the Oval Office or head back behind the microphone where he is truly in his element.